Evaluation of the tourist and agro-tourist potential of Vrancea county - Petruţa Antoneta Enache; Diana Maria Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Vrancea, the land of natural wonders, the land of old stories, the land of ancestral song and poetry unsurpassed by any Romanian land, is the most beautiful part of the Carpathian depression. This blessed land is a miniature Romania.Vrancea County has an extremely varied relief that is suitable for practicing tourist activities. The paper aims at an analysis of the tourist and agrotourism potential in Vrancea county using the following indicators: the evolution of agrotourism pensions, tourist reception structures, accommodation capacity, etc. The analysis highlighted the fact that the county has vast natural and anthropic resources that are poorly exploited for the development of tourism and agrotourism.
Keywords: L83; 330; tourist and agrotourism potential; tourist activity; accommodation capacity